Niraparib therapy in patients with newly diagnosed advanced ovarian cancer after chemotherapy: PRIMA/ENGOT-OV26/GOG-3012 study. (1st November 2019) - González-Martín, A; Pothuri, B; Vergote, I; Christensen, RD; Graybill, W; Mirza, MR; McCormick, C; Lorusso, D; Hoskins, P; Freyer, G; Baumann, K; Jardon, K; et al.
Abstract : Introduction/Background: Niraparib improves progression-free survival (PFS) in patients (pts) with newly diagnosed advanced ovarian cancer after 1st-line (1L) platinum-based chemotherapy (CT). We report the efficacy of niraparib in pts by biomarker status. Methodology: This double-blind, placebo (PBO)-controlled, phase 3 study randomized 733 pts with newly diagnosed advanced ovarian, primary peritoneal, or fallopian tube cancer with a complete or partial response (CR or PR) to 1L platinum-based CT. Stratification factors were best response to the 1L CT (CR/PR), receipt of neoadjuvant CT (yes/no), and homologous recombination status (deficient/proficient/not determined). Pts received niraparib or PBO once daily. The primary endpoint of PFS assessed by blinded independent central review was analyzed using a stratified Cox proportional hazards model and hierarchically tested in homologous recombination deficient pts, then the overall population. Results: Of 733 randomized pts (niraparib, 487; PBO, 246), 373 (51%) were homologous recombination deficient (niraparib, 247; PBO, 126) and 249 (34%) were homologous recombination proficient (niraparib, 169; PBO, 80). Overall, 35% had stage IV disease, 67% received NACT, and 31% had a PR to 1L CT. Niraparib-treated pts in all the biomarkers groups had a statistically significant and clinically meaningful benefit in PFS (table 1 ). The most common grade ≥3 adverse events were anemia (31%), thrombocytopenia (29%), and neutropenia (13%). Conclusion: Niraparib improved PFS as evidenced by reduction in the risk of recurrence or death due to any cause in the overall population of advanced ovarian cancer. No new safety signals were identified. CI=confidence interval; mut=mutated; wt=wild type Disclosure: AMG: Consulting: AstraZeneca, TESARO, Roche, Pharmamar, Clovis, Merck, Genmab, ImmunoGen, Oncoinvent AS BP, RDC: Advisory: TESARO IV: Personal: Advaxis, Eisai, MSD Belgium, Roche NV, Genmab, Roche, Pharmamar, Millennium Pharmaceuticals, Clovis, Astrazeneca NV, Tesaro, Immunogen, Sotio. Grants: Amgen, Stichting tegen Kanker, Roche. Contracted Research: Oncoinvent AS, Genmab WG: Consulting: TESARO MM: Leadership/Other ownership: Karyopharm Therapeutics, Sera Prognostics. Personal Fees: Roche, AstraZeneca, Clovis, Pfizer, TESARO, Genmab, BioCad, Sotio, Geneos Therapeutics, Merck, Oncology Venture, Seattle Genetics, Sera Prognostics, Takeda, Zailab. Grants: AstraZeneca, Clovis, Pfizer, TESARO, Boehringer Ingelheim CCM, PH, KHB, KJ, CGAV, BL, AFH, MJR-P, WHB, IB: none DL: Personal: AstraZeneca, Clovis, Genmab, Immunogen, Pharma Mar SA, Amgen, Merck. Grants: Pharma Mar SA, Merck GF: Personal: TESARO, AstraZeneca, Clovis, Roche, Bristol-Meyers Squibb, MSD, Pfizer, Novartis. Grants: AstraZeneca, Roche AR: Research funding/Advisory role: Pharmamar, Roche, Eisai, AstraZeneca, TESARO RGM: Research: Angle PLC. Consulting: Fujirebio Diagnostics REO: Advisory: Clovis, TESARO, GlaxoSmithKline FB: Advisory: TESARO, Clovis, Agenus, Merck, Eisai. Grant: Clovis, Merck, Eisai, Immunogen. Lecture: CEC Oncology MPBG: Lecture/Advisory board: TESARO, AstraZeneca, Roche, Clovis, Pharmamar, MSD. MSS: Personal: TESARO, Merck, Astra Zeneca, Clovis, Pacira Pharamceuticals. Grant: TESARO GM: Personal: AstraZeneca, TESARO. Non-Financial Support: TESARO, Roche. BJM: Speaker bureau, Grant: TESARO KS, IM, YL, DG: TESARO employee.